Forest Management in the Interface: Amenity Resources - Bruce Hull; Sarah F. Ashton; Rien M. Visser; Martha C. Monroe (EDIS)
FOR-175, a 6-page illustrated fact sheet by Bruce Hull, Sarah F. Ashton, Rien M. Visser, and Martha C. Monroe, discusses aesthetic and recreational considerations for forest management in the interface between urban and rural areas. Published by the UF School of Forest Resources and Conservation, February 2008.